A Zone of Ambiguity : The Political Economy of Cigarette Bootlegging - Hornsby, Rob (The British journal of criminology, 2007)
This paper examines the development of cigarette bootlegging within the United Kingdom by way of a case study of an entrepreneurial criminal firm which sought to capitalize upon the cigarette price disparities within the European Union, through its professional supply of contraband goods to a highly receptive UK market. The paper contends that by way of the relaxation of trading barriers via European Union legislation, an enterprising criminal firm exploited the emergence of ambiguous zones of trading opportunities within the shifting terrain of the political economy produced by European integration